ANALISIS KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PEMERINTAH KABUPATEN TANGGAMUS - Helmita -; Suryani Virginia (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
This research took an object at the Population and Civil Registration Office of the TanggamusRegency as the executor of the implementation of population administration. Problems that occur at thistime where the discipline of employees is still not optimal; in addition to competency factors andmotivation, other factors that influence employee performance are work discipline.The population in this study was 83 employees. The results of the study can be concluded thatcompetence, motivation and discipline partially or simultaneously have a significant influence onemployee performance. The coefficient of determination (R2) is 0.889. This means that the variables ofcompetence, motivation, and discipline explain the effect on employee performance by 88.9%.Competence, motivation and discipline have influence both partially and simultaneously on theperformance of employees at the Population and Civil Registration Office of the Tanggamus Regency